Measurement of transepidermal water loss, stratum corneum hydration and skin surface pH in occupational settings: A review - Jansen van Rensburg, Sané; Franken, Anja; Du Plessis, Johannes Lodewykus (Skin research and technology, 2019)
Background The skin provides a permeable barrier which may be impaired in occupational settings. Transepidermal water loss (TEWL), stratum corneum hydration (SCH) and skin surface pH (SSpH) have been used in occupational settings to predict early onset of occupational skin diseases, to measure the effectiveness of prevention strategies for occupational skin diseases, and to assess skin condition during exposure. The aim was to compare the findings, identify shortcomings in the methodology and data reporting and furthermore, to make recommendations for future studies. Materials and Methods A literature study was conducted on studies published before December 2018 to provide a review on the measurement of TEWL, SCH and SSpH in occupational settings. Results TEWL, SCH and SSpH were previously measured in a wide variety of industries. Results between studies were highly variable, due to different study designs and different anatomical positions measured. Not all of the measurement conditions were reported and variations in study objectives led to data being reported and interpreted differently for most studies. Conclusion Incomplete reporting of methodology hinders comparison of bioengineering measurements. No bioengineering method has been proven useful as a predictive tool for occupational skin diseases, however, it is useful in the acute assessment of skin condition. It is recommended that future studies on TEWL, SCH and SSpH adhere to guidelines for occupational settings as far as possible to enable comparison between studies.